Research Trends for Digital-Based Civic Education Learning on Scopus Data-Based Period 2004 - 2025: Bibliometric Analysis - Lhutfia Wahyu Safutri; Erfiani Humairah; Ikrima Maulida; Eci Anita Lestari; Cut Kumala Sari (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
Technology integration in education has changed learning, including Civic Education (PKn). This change raises the need for a systematic study to understand the direction and development of digital-based civil society research. This study uses a bibliometric approach to scientific publications indexed in the Scopus database from 2004 to 2025. The data was analyzed with the help of R-Biblioshiny, OpenRefine, and VOSviewer software to visually map research trends and patterns. There has been a significant increase in publications since 2017, with an average annual growth of 16.78%. Spain, the United States, and Indonesia are the countries with the highest publication contributions. The Journal of Citizenship Teaching & Learning and the Journal of Civics are the main sources of publications. The dominant keywords include digital citizenship, civic engagement, critical thinking, and values education. Global collaboration between researchers and institutions has been identified, although cross-border collaboration is still limited. This study provides a comprehensive overview of the dynamics of digital-based PKn research. The findings can be a strategic basis for education policy development, learning innovation, and further research.